Penyusunan Harga Pokok Produksi Pada Rumah Tempe Indonesia Dengan Metode Variable Costing dan Full Costing - Alya Triana Putri Nasaru; Shalimar Syifa Gnosis; Yuni Astuti Tri Tartiani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to calculate the cost of goods produced at Rumah Tempe Indonesia, a local tempe producer classified as a Micro, Small, and Medium Enterprise (MSME) in Bogor City. The primary focus of this research is to calculate the production cost per unit produced. A case study method with a qualitative approach was employed, involving direct observation and interviews with the management. The findings of this study are expected to provide valuable insights for the company in understanding the cost calculation using both full-cost and variable-cost methods.